The Characteristics of Family Business: A Comparative Analysis of East European Countries - Güldenkoh, Maret; Silberg, Uno (Estonian Discussions on Economic Policy, 2019)
The characteristics of family businesses in the East European regions may be associated with the distinctive regional cultures suggesting support for the presence of culturally implicit theories in family business characteristics. The research design was used to develop samples of articles for content, analyzing the characteristics of family businesses in the East European cluster. This article provides an overview and comparative analysis of East European cluster differences of Anglo, Germanic and Nordic clusters and provides recommendations for the development of the family business in the East European cluster. This analysis is of East European countries, where family business cultures and family traditions have been broken. After regaining independence, entrepreneurs started to restore previous firms and wished to continue family traditions; entrepreneurship started to develop, and many started family businesses. Family businesses have become stronger interests in East European countries